2011
DOI: 10.1080/08963568.2011.556351
|View full text |Cite
|
Sign up to set email alerts
|

“Database of the Week”: Successfully Promoting Business Databases to Faculty

Abstract: This article examines an initiative to increase the awareness and usage of the business databases available at Purdue University among the faculty and graduate students. When users are not aware of the databases that are available to them through library endeavors, they look elsewhere for the information they need. That lack of awareness and subsequent nonuse of subscription databases affect faculty, student, and even librarian success. The ensuing low usage statistics result in high cost-per-use figures and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Generally, library promotional efforts are the initiative in making the users aware of the current library update and development. [13] stated that promotion of library services and activities should include specific methods such as Web 2.0 applications. A Similar study by [14] also indicated that Web 2.0 are actively used in library promotion in Pakistan libraries.…”
Section: Promoting Library Servicesmentioning
confidence: 99%
“…Generally, library promotional efforts are the initiative in making the users aware of the current library update and development. [13] stated that promotion of library services and activities should include specific methods such as Web 2.0 applications. A Similar study by [14] also indicated that Web 2.0 are actively used in library promotion in Pakistan libraries.…”
Section: Promoting Library Servicesmentioning
confidence: 99%
“…Collectively, the authors described several paths libraries might take with their marketing efforts, including handing out promotional materials, such as pens, pencils, and magnets (Brannon, 2007); displaying themed posters and panels for library resources, services, and collections (Empey & Black, 2005); and sending promotional e-mails to faculty (Dugan, 2011). The varied marketing paths reflect the different objectives libraries may have in undertaking marketing campaigns.…”
Section: Promoting Discoverymentioning
confidence: 99%
“…Betz et al (2009) report on promoting the use of Scopus and Web of Science, to graduate students on campus. Dugan (2011) reports on an initiative to increase the awareness and usage of business databases available at Purdue University among faculty and graduate students, while Duke et al (2009), discussing a project on collaborating with students in marketing databases, found that student-generated surveys and marketing ideas proved useful. Often marketing efforts are linked to training sessions (Henderson et al,.…”
Section: In Terms Of Targeting Users -What Is Suggested In the Lis LImentioning
confidence: 99%
“…Often studies are limited to the use of products and services, or aligned with attempts to promote the use of products and library services (Smith, 2011). Inadequate use of databases is often ascribed to lack of awareness (Dugan, 2011). Betz et al (2009) report on promoting the use of Scopus and Web of Science, to graduate students on campus.…”
Section: In Terms Of Targeting Users -What Is Suggested In the Lis LImentioning
confidence: 99%